Prevalence of Obesity among Undergraduate Students of Tai Solarin University of Education, Ijagun, Ijebu-Ode - Olusanya, J.O.; Omotayo, O.A. (Pakistan Journal of Nutrition, 2011)
In recent years, developing countries like Nigeria have been experiencing a nutritional transition in food choices from the typical starchy (mainly carbohydrate diets) to the fast food pattern and as a result of this, the dietary habits of young adults like university students have been affected. Thus, overweight and obesity are increasingly being observed among the young adults. This study assesses the prevalence of obesity on a sample of students from Tai Solarin University of Education in Ijebu-Ode, Ogun State, Nigeria. 371 students were randomly sampled from 100 level to 400 level between ages 16 and 27 years old. 151 male students (40.7%) and 220 female students (59.3%) made up the population. Daily intake of snacks apart from regular meals was more common among females than males (79.5% vs. 70.6% respectively). More female students engaged in physical exercise and reading (16.4% and 36.1% respectively) as compared with male (11.1% and 22.9% respectively). Based on BMI classification, the prevalence of overweight and obesity was more common among female students compared to male (10% and 5.1% vs. 4.6% and 1.3% respectively). Also, the findings revealed that age is the most potent predictor of obesity followed by gender while family background and recreational activities did not significantly predict obesity. Thus, this study should provide incentive for the private and public sectors to mobilize all available resources to stem the tide of increasing body mass index in university students and adults. Also, public health strategies to prevent obesity should begin with schools and extend to the entire community.